30-Day Mortality Following Palliative Radiotherapy - Vázquez, Miriam; Altabas, Manuel; Moreno, Diana C.; Geng, Abraham A.; Pérez-Hoyos, Santiago; Giralt, Jordi (Frontiers in Oncology, 2021)
Purpose: 30-Day Mortality (30-DM) is a parameter with widespread use as an indicator of avoidance of harm used in medicine. Our objective is to determine the 30-DM followed by palliative radiation therapy (RT) in our department and to identify potential prognosis factors. Material/Methods: We conducted a retrospective cohort study including patients treated with palliative RT in our center during 2018 and 2019. Data related to clinical and treatment characteristics were collected. Results: We treated 708 patients to whom 992 palliative irradiations were delivered. The most frequent primary tumor sites were lung (31%), breast (14.8%) and gastrointestinal (14.8%). Bone was the predominant location of the treatment (56%) and the use of single doses was the preferred treatment schedule (34.4%). The 30-DM was 17.5%. For those who died in the first month the median survival was 17 days. Factors with a significant impact on 30-DM were: male gender (p<0.0001); Eastern Cooperative Oncology Group (ECOG) Performance Status (PS) of 2-3 (p=0.0001); visceral metastases (p=0.0353); lung, gastrointestinal or urinary tract primary tumors (p=0.016); and single dose RT (p=<0.0001). In the multivariate analysis, male gender, ECOG PS 2-3, gastrointestinal and lung cancer were found to be independent factors related to 30-DM. Conclusion: our 30-DM is similar to previous studies. We have found four clinical factors related to 30-DM of which ECOG was the most strongly associated. This data may help to identify terminally ill patients with poor prognosis in order to avoid unnecessary treatments.